the Mapping Digital Competence Research in Pre-Service Science Teacher Education through a Scopus-Based Bibliometric Analysis (2020–2025) - Nuri Nuri; Putut Marwoto; Bambang Subali; Sulhadi Sulhadi; Lanidana Etni Laos (ISEJ : Indonesian Science Education Journal, 2026)
Post-pandemic digital transformation in education requires pre-service science teachers to have strong digital competencies. However, previous studies remain fragmented and have not fully integrated digital learning models with digital competence development. This study aims to map global research trends, identify the intellectual structure, and explore research gaps in this field. A quantitative bibliometric approach was conducted using Scopus-indexed publications from 2020–2025. A total of 30 documents were selected through the PRISMA procedure and analyzed using Bibliometrix (R). The findings show an increasing publication trend, especially in 2021 during the global shift to digital learning. Research was mainly dominated by Asian and European countries, while contributions from developing countries remained limited. Major themes included TPACK, pedagogical innovation, pre-service teacher education, and 21st-century competencies. However, the connection between digital learning design and digital competence development is still limited. This study emphasizes the need for an integrative and sustainable digital learning framework to support the transformation of science teacher education.